Character formation from a psychological point of view: search for values, search for “Sinn” - Funke, Joachim (Heidelberger Jahrbücher online, 2020)
Character formation has a lot to do with the development of moral values. Classical as well as modern conceptions of moral development will be presented here. Additionally, a world view on values shows that there is a significant convergence on human values in different cultures. Also, the connection between moral values and wisdom is discussed. Measurement approaches to moral values are listed and commented on. Finally, some results from recent “trolley dilemmata” will be presented and evaluated concerning issues of moral judgments.
Gesehen am 22.07.2020